ย้อนวิเคราะห์แนวโน้มการฟ้องคดีต่อศาลปกครองของคณะสงฆ์ - ดีอด, พงษ์มนัส (วารสารมหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน, 2020)
ศาลปกครองถือได้ว่าเป็นศาลที่พิจารณาคดีเกี่ยวเกี่ยวกับการดำเนินงานของเจ้าหน้าที่ทางปกครองที่ปฏิบัติหน้าที่ที่ไม่ชอบด้วยกฎหมาย หรือละเมิดต่อกฎหมาย ซึ่งประชาชนหรือเจ้าหน้าที่ของรัฐหรือหน่วยงานทางปกครองมีอำนาจในการฟ้องของใช้สิทธิในการยื่นฟ้องคดีต่อศาลปกครองให้พิจารณาได้ได้ โดยการศึกษาย้อนพิเคราะห์แนวคำพิพากษาศาลปกครองของคณะสงฆ์ถือได้ว่ามีวัตถุประสงค์ เพื่อศึกษาถึงปรากฎการณ์และสาเหตุของการฟ้องร้องคดีของคณะสงฆ์ต่อศาลปกครอง รวมทั้งสาเหตุของการฟ้องร้องคดีต่อศาลปกครอง ทั้งนี้การฟ้องร้องคดีต่อศาลปกครองของคณะสงฆ์ในที่นี่มีความหมายรวมถึงการ การที่พระสงฆ์ ซึ่งเป็นบุคคลธรรมดา และรวมทั้ง วัด ซึ่งเป็นนิติบุคคลเป็นผู้ยื่นฟ้องเป็น โจทก์และจำเลยด้วย โดยใช้แนวคำสั่งของศาลปกครอง และแนวคำวินิจฉัยของศาลปกครอง ตั้งแต่ปี พ.ศ. 2543 – พ.ศ. 2563 รวมเป็นระยะเวลา 20 ปี ซึ่งจากการศึกษาพบว่าตลอดระยะเวลา 20 ปีดังกล่าว การฟ้องคดีต่อศาลปกครองของคณะสงฆ์มีแนวโน้มที่ลดลง และคณะสงค์มีการใช้สิทธิทางศาลปกครองเพื่อยื่นคำฟ้องต่อศาลปกครองเป็นจำนวนมากที่สุดโดยอาศัยสิทธิในการยื่นฟ้องตามมาตรา 9 อนุมาตราหนึ่งเป้นจำนวนมากกว่าอนุมาตรอื่นเนื่องมาจาก โดยคดีส่วนมากของทางคณะสงฆ์เป็นการฟ้องคดีพิพาทที่เกี่ยวกับการจัดการที่ดินและปัญหาที่เกิดขึ้นจากการใช้ที่ดินส่งผลให้มีความเกี่ยวข้องกับมาตรดังกล่าว ทั้งนี้พบว่าในประการแรกที่คดีของคณะสงฆ์มีจำนวนน้อยลงอาจเกิดขึ้นจากมีกระบวนการยุติธรรมทางเลือกหรือการพิจารณาที่เป็นการไกล่เกลี่ยก่อนฟ้องศาล อีกทั้งประการที่สองปัญหาที่มีการใช้สิทธิในการยื่นฟ้องข้อพิพาทที่เกี่ยวกับการจัดการที่ดินและปัญหาที่เกิดขึ้นจากการใช้ที่ดินเนื่องมาจากที่ดินวัดถือได้ว่าเป็นสาธารณะสมบัติของแผ่นดินส่งผลเกิดเมื่อมีการบริจาคแล้วเกิดปัญหาการใช้ที่ดินต่าง ๆ ตามมาได้อีกหลายประการ   Abstract           The administrative court is considered to be a court for considering the case about the operation of the administrative staff that illegally operates their works which population or government officers or administrative department has a right to make an accusation to the administrative court for consideration by studying retrospective analysis of the judgment from the administrative court, which aims to study the occurrence and causes of the accusation of the monk party to the administrative court, including the causes of accusation to the administrative court. However, the accusation of the monk party to administrative court also includes the fact that a monk, who is considered to be a normal person, and a temple who is a juristic person, complainant, and defendant by using a judgment guideline and synthesis guideline from the administrative court from 2000 to 2020, which is 20 years in total. According to the study from those twenty years as mentioned, the trend of the accusation of monk party to administrative court has been decreased, and monk party has utilized the right from the administrative court for the most by using a right for making an accusation in accordance with section 9, subsection 1 rather than other subsections since most cases from monk party are disputation about land management and the problems from land usage which leads to the correspondence of that section. Nevertheless, it can be seen that the first reason for the reduction of the monk party’s case is that there is an alternative justice process of the consideration that is reconciliation before making an accusation to the court. Moreover, the second reason is that the problem of right usage for making an accusation about land management and the problems from land usage is caused from the fact that temple land is considered to be a public national property which is constructed from donations and many problems from land usage can occur afterward.